662 ENHANCING CARE BY IMPROVING DISCHARGE SUMMARIES. (8th March 2022) - Davidson, C; Zaw, M K; Loh, R; Grout, C
Abstract: Introduction: Within the Geriatric Medicine department at the Lister Hospital, Stevenage, the timeliness and quality of discharge summaries had become a source of complaints. Both primary care practitioners and families reported documentation was inadequate or incorrect. This project aimed to improve the quality of these discharge summaries in accordance with standards generated from previous audit data. Through improving communication it was clear that patient care could be enhanced. Methods: Each month 15 discharge summaries were selected at random for review. Alongside patient notes these summaries were appraised in regards to standard discharge summary requirements: timeliness of delivery; adequate description of admission; and documentation of the follow up plan. They were also appraised on documentation of specific requirements for older aged adults including cognitive status, mobility status, discharge destination, need for home help, Rockwood Frailty score and resuscitation and escalation plans. Interventions including informal communication with junior doctors, circulation of a 'Top Tips' sheet, generation of an information poster and dissemination of information at local teaching sessions, took place, and were assessed, over regular PDSA cycles. Results: showed a clear, sustained improvement in the quality of the discharge summaries. At the end of data collection, 100% of discharge summaries contained an adequate description of admission and an appropriate follow up plan. There was also significant improvement in documentation of specific requirements. Where documentation was initially very limited, following interventions, most discharge summaries contained details pertaining to discharge destination, need for home support, mobility status and resuscitation and escalation plans. Conclusion: The relatively simple interventions have been found to have a sustained improvement in the quality of discharge summaries from the Geriatric Medicine Department at Lister Hospital, Stevenage. Whilst more work needs to be done it is hoped that this will already have enhanced patient care.